TRADISI MASYARAKAT NELAYAN RAWA PENING KELURAHAN BEJALEN KECAMATAN AMBARAWA KABUPATEN SEMARANG - Cristianawati Cristianawati (Sabda: Jurnal Kajian Kebudayaan, 2017)
Bejalen village is located in Ambarawa subdistrict which has 470,720 hectars. There are 14,040 hectars of ponds and about 86 hectars rice fields as a good source for fish and agritultural production. The agricultural output reached 14,040 tons of crops and the production of fish amounted 1,533 tons. The Livelihood of community is fishermen. They work everyday based on the old generation tradition. The research purpose has gained more information about the fishermen culture, such as social, economic, and organisational condition.